Pengaruh Budaya Organisasi Terhadap Kinerja Guru Dengan Motivasi Sebagai Variabel Interving - Nabila Ariani; Sumarni; Hendriyaldi (Jurnal Publikasi Ilmu Manajemen, 2024)
. A teacher is a professional staff in the field of education whose job is to guide, teach, train, direct and educate the life of the nation. This research aims to see the influence of organizational culture on teacher performance with motivation as an intervening variable at SMP Negeri 21 Tanjung Jabung Timur. This research uses descriptive quantitative methods with data collection techniques using questionnaires. The population and sample in this study were 30 teachers at SMP Negeri 21 Tanjung Jabung Timur. Hypothesis testing using the SmartPLS analysis tool. The results of this research show that organizational culture has a positive and significant effect on teacher performance, organizational culture has a positive and significant effect on motivation, motivation has a positive and significant effect on teacher performance, organizational culture has a positive and significant effect on teacher performance with motivation as an intervening variable. This proves that an organization with a strong culture will improve the quality of teacher performance, and is further strengthened by providing motivation so that teacher performance will be maximized.